Introduction: Critical Agrarian Studies in Theory and Practice: Symposium: Agrarianism in Theory and Practice Organisers: Jennifer Baka, Aaron Jakes, Greta Marchesi and Sara Safransky. Issue 4 (24th April 2017) - Edelman, Marc; Wolford, Wendy
Abstract: In this introductory article we argue for renewed attention to life and labor on and of the land—or what we call the field of Critical Agrarian Studies. Empirically rich and theoretically rigorous studies of humanity's relationship to "soil" remain essential not just for historical analysis but for understanding urgent contemporary crises, including widespread food insecurity, climate change, the proliferation of environmental refugees, growing corporate power and threats to biodiversity. The article introduces an innovative and varied collection of works in Critical Agrarian Studies and also examines the intellectual and political history of this broader field.